2013
DOI: 10.3329/bjp.v8i3.14521
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of potential cholesterol esterase inhibitors using <i>in silico</i> docking studies

Abstract: New drug discovery is considered broadly in terms of two kinds of investigational activities such as exploration and exploitation. This study deals with the evaluation of the cholesterol esterase inhibitory activity of flavonoids apigenin, biochanin, curcumin, diosmetin, epipervilline, glycitein, okanin, rhamnazin and tangeritin using in silico docking studies. In silico docking studies were carried out using AutoDock 4.2, based on the Lamarckian genetic algorithm principle. The results showed that all the sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…It is probably because of its higher polyphenol compounds, which has been demonstrated to possess an ability to bind to the active protein pocket of the enzyme [4,24]. Various assays also revealed that many plant polyphenols and flavonoids possess in vitro inhibitory activities of cholesterol esterase [25] and carbohydrate hydrolyzing enzymes [26,27].…”
Section: In Vitro α-Amylase and α-Glucosidase Inhibitory Activitymentioning
confidence: 99%
“…It is probably because of its higher polyphenol compounds, which has been demonstrated to possess an ability to bind to the active protein pocket of the enzyme [4,24]. Various assays also revealed that many plant polyphenols and flavonoids possess in vitro inhibitory activities of cholesterol esterase [25] and carbohydrate hydrolyzing enzymes [26,27].…”
Section: In Vitro α-Amylase and α-Glucosidase Inhibitory Activitymentioning
confidence: 99%
“…Few reports have revealed the inhibitory property of gallic acid, mangiferin, catechin, epicatechin, procyanidins, and saponins from herbal extracts against CEase (30)(31)(32). The in silico docking studies on a few flavonoids such as apigenin, curcumin, glycitein, okanin, and rhamnazin also documented the presence of potent CEase inhibitory sites, especially the interaction with the catalytic triad and oxyanion hole residues (33). We assume that an approximately similar mechanism may be adopted by phenolic acids.…”
Section: Resultsmentioning
confidence: 61%
“…A study deals with the evaluation of the cholesterol esterase inhibitory activity of biochanin-A using in silico docking approach. Biochanin-A contributed cholesterol esterase inhibitory activity, these molecular docking analyses could lead to the further development of potent cholesterol esterase inhibitors for the treatment of obesity (Sivashanmugam et al, 2013).…”
Section: Obesitymentioning
confidence: 99%